Enhanced Pheromone-based Mechanism to Coordinate UAVs and WSN Nodes on the Ground - Heimfarth, Tales; de Freitas, Edison Pignaton; Netto, Ivayr Farah; Correia, Luiz H. A.; Pereira, Carlos Eduardo; Ferreira, Armando Morado; Wagner, Flávio Rech; Larsson, Tony (INFOCOMP Journal of Computer Science, 2010)
This paper presents a step forward of a pheromone-based mechanism used to coordinate Unmanned Aerial Vehicles (UAVs) andWireless Sensor Networks (WSNs) on ground that together compose a surveillance system to detect and acquire information of possible targets in an area of interest. The proposed enhancement aims at to diminish the overhead in terms of communication needed to provide the desired coordination among these different nodes that compose the network. This is done by means of a more efficient UAV pheromone information distribution among the sensor nodes on the ground. Simulation results are presented comparing the proposed enhancement with the original mechanism, denoting the advantage of the enhanced one.